On the path to better nutrition and health : A4NH 2012 annual report - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2013)
In its first year, A4NH took many steps to lay the groundwork for improved global health and nutrition in the future. Our initial work focused on solidifying critical partnerships, establishing a management structure that will provide external guidance and advice, developing our partnership and gender strategies, and planning for exciting new research initiatives in our four program areas. Besides establishing a coordinated governance and oversight structure, many A4NH research programs were already underway in 2012, particularly those focusing on biofortification, sustainable diets, and agriculture-associated diseases.